THE EFFECT OF WARM WATER SOAK FOR HYPERTENSION IN ELDERLY IN POSYANDU PONDOK JERUK TAMBAKBERAS, TAMBAKREJO VILLAGE, JOMBANG DISTRICT, JOMBANG DISTRICT - Santoso, Shelfi Dwi Retnani Putri; Hidayah, Siti Nur; Sasmito, Nanang Bagus (WELL BEING, 2019)
Hypertension is a common disease in the elderly. Hypertension can be treated with non-pharmacology such as soaking foot warm water which is useful for dilating blood vessels so that blood circulation. The purpose of this study is to identify blood pressure levels before and after the intervention and analyze the effect of giving warm water soak. The research design used a quasi-experimental design with a pre-test-posttest control group design. The sampling technique uses purposive non probability sampling with a population of 32 people and a sample of 20 people. The results of the pretest-posttest cystole showed a value of 0.001 (P <0.005) and the result of the pretest-posttest diastole showed a decrease in difference indicated by the value of 0.002 (P <0.005). The statistical test used Paired T-Test. So that, there is a significant influence on the decrease in systolic and diastolic blood pressure before and after warm water foot bath therapy. Keywords: Foot Warm Water Soak, Hypertension, Elderly